The work of global justice: Human rights as practices - Fuyuki, Kurasawa (Cambridge University, 2013)
Human rights have been generally understood as juridical products, organizational outcomes or abstract principles that are realized through formal means such as passing laws, creating institutions or formulating ideals. In this book, Fuyuki Kurasawa argues that we must reverse this 'top-down' focus by examining how groups and persons struggling against global injustices construct and enact human rights through five transnational forms of ethico-political practice: bearing witness, forgiveness, foresight, aid and solidarity. From these, he develops a new perspective highlighting the difficult social labour that constitutes the substance of what global justice is and ought to be, thereby reframing the terms of debates about human rights and providing the outlines of a critical cosmopolitanism centred around emancipatory struggles for an alternative globalization.